Development of the Assessment Criteria and Validation of Twak Sarata (AYUSHDHARA, 2022)
Introduction: Sara Parikshana is the one used to evaluate every Dhatu & to understand physical strength as well as mind strength. For assessing Twak Sarata, it was necessary to develop assessment criteria for evolution of Twak Sarata. Aim and objectives: To explore, develop assessment criteria and survey study regarding Twak Sarata. Material and Method: 100 Twak Sara individuals were selected after screening process for Twak Sarata in total 428 apparently healthy individuals. Subjective & objective parameters were observed on these selected individuals. Then, possible scoring of objective parameters has been done and spearman’s correlation test is applied to check the relation between Subjective & objective parameters. Results: Characteristics of Twak Sarata were found significant when KS test was applied. There was significant relation found between parameters like Snigdha and moisture meter test readings, Snigdha and Hair thickness, Loma Sukumarata and Hair thickness. Conclusion: Snigdhata of Twak Sara individuals assessed objectively by moisture meter test and normal range was in between 30-50% for Twak Sara Purusha. Snigdhata & Sukumarata of Loma of Twak Sara Purusha assessed objectively by hair thickness objective parameter by using micro-meter hair dial gauze and range was